Overcoming High Cardiovascular Disease Burden in Indonesia: The Importance of Massive Cardiovascular Disease Risk Factor Screening, Aggressive Guideline-Directed Treatment, and Community-Based Programs - Yoga Waranugraha (Heart Science Journal, 2022)
Indonesia is a developing country with a large number of populations. Cardiovascular disease (CVD) is a serious public health concern in Indonesia because of its high burden. Moreover, the high-risk CVD patients were under treatment. Optimal CVD prevention can be the solution to this issue. In this paper, we are talking mainly about the role of massive CVD risk factor screening, precise risk stratification, aggressive guideline-directed treatment, and community-based programs in reducing the CVD burden.